The preparation period in basketball: Training load and neuromuscular adaptations - Ferioli, D.; Bosio, A.; Bilsborough, J. C.; La Torre, A.; Tornaghi, M.; Rampinini, E. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To investigate the effect of the preparation period on neuromuscular characteristics of 12 professional (PRO) and 16 semiprofessional (SEMIPRO) basketball players and relationships between training-load indices and changes in neuromuscular physical performance. Methods: Before and after the preparation period, players underwent a countermovement jump (CMJ) test followed by a repeated change-of-direction (COD) test consisting of 4 levels with increasing intensities. The peripheral neuromuscular functions of the knee extensors (peak torque [PT]) were measured using electrical stimulations after each level (PT1, PT2, PT3, and PT4). Furthermore, PT Max (the highest value of PT) and PT Dec (PT decrement from PT Max to PT4) were calculated. Results: Trivial to small (effect size [ES]=-0.17 to 0.46) improvements were found in CMJ variables, regardless of competitive level. After the preparation period, peripheral fatigue induced by a COD test was similarly reduced in both PRO (PT Dec: from 27.8% [21.3%] to 11.4% [13.7%]; ES=-0.71; 90% confidence interval [CI], ±0.30) and SEMIPRO (PT Dec: from 26.1% [21.9%] to 10.2% [8.2%]; ES=-0.69; 90% CI, ±0.32). Moderate to large relationships were found between session rating of perceived exertion training load and changes in peak power output (PPO) measured during the CMJs (rs [90% confidence interval]: PPOabs, -.46 [±.26]; PPOrel, -.53 [±.23]) and in some PTs measured during the COD test (PT1, -.45 [±.26]; PT2, -.44 [±.26]; PT3, -.40 [±.27]; and PT Max, -.38 [±.28]). Conclusions: The preparation period induced minimal changes in the CMJ, while the ability to sustain repeated COD efforts was improved. Reaching high session rating of perceived exertion training loads might partially and negatively affect the ability to produce strength and power.